CT perfusion-guided patient selection for endovascular treatment of acute ischemic stroke is safe and effective. (19th September 2011) - Turk, Aquilla; Magarik, Jordan Asher; Chaudry, Imran; Turner, Raymond D; Nicholas, Joyce; Holmstedt, Christine A; Chalela, Julio; Hays, Angela; Lazaridis, Christos; Jauch, Edward; Chimowitz, Marc; Turan, Tanya; et al.
Abstract : Background: Traditional treatment in acute ischemic stroke is based on time criteria when administering intravenous and intra-arterial therapies. However, recent evidence suggests that image-based criteria may be useful for selecting patients for intra-arterial interventions. The use of CT perfusion (CTP)-based criteria, regardless of time from symptom onset, in patient selection for intra-arterial treatment of ischemic stroke was assessed. Methods: Patients with ischemic stroke who presented to the emergency department at the Medical University of South Carolina with a National Institute of Health Stroke Scale score of ≥ 8, regardless of time from symptom onset, were assessed retrospectively. CTP maps were qualitatively assessed for the presence of penumbra and infarction. Selected patients underwent mechanical aspiration of their occlusion using the Penumbra system. Functional outcome was then recorded using the modified Rankin scale (mRS) at 90 days or the closest follow-up to 90 days. Results: 53 patients were included in the study. The median time from symptom onset to groin vascular access was 6.3 h. Eight patients (15%) had bleeding complications including subarachnoid hemorrhage, parenchymal hemorrhage and intraventricular hemorrhage. After CTP-based selection, the patients were divided into two groups for analysis: ≤6 h and >6 h from symptom onset to endovascular procedure. No difference was found in functional outcome between the two groups (38.5% and 40.7% achieved 90-day mRS ≤2, respectively (p=1.0) and 57.7% and 51.9% achieved 90-day mRS ≤3, respectively (p=0.785)). There was no difference in the rate of intracranial hemorrhage between the two groups (11.5 vs 18.5, p=0.704). Conclusion: This study demonstrated similar rates of good functional outcome and intracranial hemorrhage in patients with ischemic stroke when endovascular treatment was performed based on CTP selection rather than time-guided selection. These findings suggest that endovascular reperfusion in ischemic stroke may be effective and safe, and may allow patient selection not solely based on time from symptom onset.